Development, recovery and evaluation of fresh mushroom chips and mushroom fortified noodles - Desayi, D B; Kukanoor, L H; Patil, C P; Shirur, Mahantesh; Shivakumar, B B (Mushroom Research, 2011)
Among the different treatments fresh mushroom chips prepared by soaking in one per cent salt+ one per cent KMS+0.5 per cent citric acid for five minutes along with partial dehydration for two minutes recorded higher per cent recovery, lower oil uptake, higher scores for organoleptic characters like colour and appearance, flavour, crispness, taste and overall acceptability. Among the different treatments 15 per cent mushroom powder fortified with noodle flour recorded the highest scores for organoleptic parameters like colour and appearance, flavour, crispness, taste and overall acceptability. Fortification of 20 percent mushroom powder to the noodle flour was found better for mushroom fortified noodles.